The Australia 2020 Summit – Few New Ideas but Moving Australia to the Left - Bateman, Sam (2016)
The Australia 2020 Summit was convened by Prime Minister Kevin Rudd to explore the challenges facing Australia over the next decade, and to capture new ideas to respond to them. Despite its lofty aims, the summit produced little that was new but the symbolism of the event was important, including signals that the Rudd Government is moving to the Left.